If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -72 = 96 + -9x Reorder the terms: -72 + -3x = 96 + -9x Solving -72 + -3x = 96 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -72 + -3x + 9x = 96 + -9x + 9x Combine like terms: -3x + 9x = 6x -72 + 6x = 96 + -9x + 9x Combine like terms: -9x + 9x = 0 -72 + 6x = 96 + 0 -72 + 6x = 96 Add '72' to each side of the equation. -72 + 72 + 6x = 96 + 72 Combine like terms: -72 + 72 = 0 0 + 6x = 96 + 72 6x = 96 + 72 Combine like terms: 96 + 72 = 168 6x = 168 Divide each side by '6'. x = 28 Simplifying x = 28
| r-8=-32 | | W=0.3d-0.56 | | -104+3x=10x+50 | | 4(7m-1)+3(2-5m)=4(3m+5)-6 | | 0.3+5-3+0.1x=0.2(x-6) | | -201+12x=51-6x | | .20x+3y+3=2x-14y | | 14x-(5x+6)+16=4x | | 9-4x=17+4x | | 7x+9=9x+7 | | b=8m+9 | | 8x=26+14y | | 18-2x+x=6x-3 | | 90+45w=960 | | -132+2x=-6x+44 | | (x+2)-4=-3x+12 | | 4w+7x-13y+5w+5x+7y= | | 4y-2(4)=16 | | 42=14y-7y | | -132+2x=10x+50 | | 5+x+3x=4x+5 | | (2x^2+11x-18)=0 | | -6x-78=57-x | | 10=6y+2+3y+17 | | 4+3+2+6+10= | | 4(x-1)=5.6 | | 2(m-22)+3(m-4)=36 | | 1.4(5x-0.2)= | | x+-39=-2x+33 | | 25(2x^2+11x-18)=0 | | z-39=-2x+33 | | 40-5w=3w |